MEDEA: a DSGE model for the Spanish economy - Pablo Burriel; Jesús Fernández-Villaverde; Juan F. Rubio-Ramírez (SERIEs - Journal of the Spanish Economic Association, 2010)
In this paper, we provide a brief introduction to a new macroeconometric model of the Spanish economy named MEDEA (Modelo de EquilibrioDinámico de la Economía Espa\~nolA). MEDEA is a dynamic stochastic general equilibrium (DSGE) model that aims to describe the main features of the Spanish economy for policy analysis, counterfactual exercises, and forecasting. MEDEA is built in the tradition of New Keynesian models with real and nominal rigidities, but it also incorporates aspects such as a small open economy framework, an outside monetary authority such as the ECB, and population growth, factors that are important in accounting for aggregate fluctuations in Spain. The model is estimated with Bayesian techniques and data from the last two decades. Beyond describing the properties of the model, we perform different exercises to illustrate the potential of MEDEA, including historical decompositions, long-run and short-run simulations, and counterfactual experiments.
Keywords: C11; C13; E30; 330; DSGE models; likelihood estimation; Bayesian methods; Ökonometrisches Makromodell; Dynamisches Gleichgewicht; Schätztheorie; Spanien